La motivación en los procedimientos de selección y adjudicación de contratos y concesiones administrativas - Rocío Navarro González (Revista Vasca de Administración Pública)
The recent Act 39/2015 of October 1st on the Common Administrative Procedure of Public Administrations has not led to substantive changes regarding the requirement of motivating acts that resolve selective and competitive procedures, which has to be delivered according to the provisions that rule the calls, certifying at the same time the grounds on which the resolution is adopted either with an individual motivation for each interested part or with reference to the file. On the basis of the analysis of the different phases in public procurement procedures, it is observed that motivation apart from qualifying as a true and inexcusable guarantee keeps its permanent and transversal presence in those specific procedures that remark its different and significant peculiarities.